Кореляція витрат у багаторубіжних системах захисту інформації - Levchenko, Ye. G.; Rabchun, D. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2015)
Economic optimization problems of information security are aimed at addressing two major problems: determining the optimal amount of investment in information security, which provides the best economic performance and optimizing the resource allocation between objects. The transition to multilevel multi-barrier systems significantly expands the problem and raises a number of issues arising from the complexity of the structure and physical layout of individual items. We consider a series-parallel layout of obstacles, which contains common obstacles for all objects and individual obstacles. The feasibility of introducing of an additional obstacle at the constant information security budget, depending on vulnerabilities of obstacles and the information distribution between objects, was analyzed. The method was developed and the results of calculations of optimal allocation of resources between the common and individual barriers were presented. Conditions of correlation were considered between the optimal allocation of resources aimed at individual obstacles. The results may be useful in developing recommendations for the creation of optimal information security systems and the resources management.